A study on lift maintenance in UiTM Shah Alam / Fatimah Abdul Rahim - Abdul Rahim, Fatimah (Faculty of Architecture, Planning and Surveying, 2015)
The maintenance of building faculty’s lift services are very important to ensure the security level and user convenience. However, there have many problems of lift maintenance works. There are many complaints were made on maintenance services weakness which is operate in ever building in uitm that researcher study. Lift expended at at the UiTM buildings often damaged and this may caused various problems to make maintenance and also occupants. To answer these problems, a study maintenance lift at UiTM of the faculty buildings to identify the lift maintenance problem and to suggest the best maintenance at UiTM’s buildings. About 5 building were identified in UiTM SHAH ALAM were chosen. For each building, the respondents are 30 persons and one respondents of maintenance management in that building. Questionnaire forms are used to obtained information about objective of the study. This study used to make an analytical frequency to analyze the data. Study found that the main problems which normally faced by maintenance worker during maintenance work implemented was lack of skilled labour and employees attitude who were not carry out their task nicely. As such, this study also obtains the best lift maintenance at building UiTM and followed the requirement.